Randomized Trial of Antibiotics in Addition to Tocolytic Therapy to Treat Preterm Labor - D. Heather Watts; Marijane A. Krohn; Sharon L. Hillier; David A. Eschenbach (Hindawi Limited, 1994)
Objective: The objective of this study was to assess whether antibiotic therapy plus tocolysis given to women in preterm labor would prolong pregnancy compared with tocolysis alone.